O Relatório de Impacto Ambiental como fonte de informação: um estudo sobre sua disponibilidade online pelos órgãos ambientais sediados em Belém - CONCEIÇÃO, Josué Rodrigues da (2017)
Study on the availability and accessibility of the Environmental Impact Report (RIMA) online by the environmental agencies headquartered in Belém, whose main objective is to verify if there is a disclosure of the RIMA by the bodies that have the responsibility and competence to grant environmental licensing in the cases of companies Which cause significant environmental impacts. It is known that economic development depends to a large extent on the exploitation of existing resources in the environment. These actions, when carried out in an indiscriminate manner, cause various types of damages to nature, demanding from all social segments attitudes to guarantee the preservation of the environment, through the elaboration of public policies, for example, as the provision of environmental information. Access to information, contained in documents such as RIMA, is essential to increase the participation of the population in the process of building a healthy and more balanced environment. RIMAs are sources of information for decision-making and environmental awareness. In order to reach the proposed objective, a bibliographical research was developed for the study of the work, using the exploratory research, where a search on the proposed theme was carried out and a descriptive study of the IBAMA, SEMA and SEMMA sites, in order to verify the Existence of such documents. It can be verified that in some environmental organs there is still no online availability of RIMA. It is concluded, therefore, that RIMA needs to be widely disseminated so that society can take cognizance of environmental impacts, since it is a source of environmental information essential for this purpose in order to reach a larger number of people.